Methods in Quaternary Ecology #3. Plant Macrofossils - Warner, Barry (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary Plant macrofossils consist of reproductive and vegetative plant parts visible to the un-aided eye. Lakes and peat lands are the most common repositories for the preservation of Quaternary plant macrofossils; however, natural tar seeps, calcareous nodules,spring deposits, packrat middens, and fossil dung are important sources of plant remains also. In Canada, the first plant macrofossils were collected in the mid-1800s, with a brief period of activity around 1900 before the beginning of modern Quaternary plant macrofossil analyses around 1960. Taphonomic studies indicate that plant macrofossils can be transported, sorted and redeposited long distances, which complicates paleoecological reconstructions. Plant macrofossils are valuable in geological studies of environmental history and climatic change; however, the use of plant macro-fossils for biostratigraphic correlation must await further research. Four broad phyto-geographic patterns are recognizable on the basis of Quaternary plant macrofossil records in Canada, and plant macrofossils can be used to trace the evolutionary origins of the modern flora.